Clinical Practice Guidelines for the Perioperative Nutrition, Metabolic, and Nonsurgical Support of Patients Undergoing Bariatric Procedures – 2019 Update: Cosponsored by American Association of Clinical Endocrinologists/American College of Endocrinology, The Obesity Society, American Society for Metabolic and Bariatric Surgery, Obesity Medicine Association, and American Society of Anesthesiologists. Issue 4 (23rd March 2020) - Mechanick, Jeffrey I.; Apovian, Caroline; Brethauer, Stacy; Timothy Garvey, W.; Joffe, Aaron M.; Kim, Julie; Kushner, Robert F.; Lindquist, Richard; Pessah‐Pollack, Rachel; Seger, Jennifer; Urman, Richard D.; Adams, Stephanie; et al.
Abstract : Objective: The development of these updated clinical practice guidelines (CPGs) was commissioned by the American Association of Clinical Endocrinologists (AACE), The Obesity Society (TOS), American Society for Metabolic and Bariatric Surgery (ASMBS), Obesity Medicine Association (OMA), and American Society of Anesthesiologists (ASA) Boards of Directors in adherence with the AACE 2017 protocol for standardized production of CPGs, algorithms, and checklists. Methods: Each recommendation was evaluated and updated based on new evidence from 2013 to the present and subjective factors provided by experts. Results: New or updated topics in this CPG include: contextualization in an adiposity‐based chronic disease complications‐centric model, nuance‐based and algorithm/checklist‐assisted clinical decision‐making about procedure selection, novel bariatric procedures, enhanced recovery after bariatric surgery protocols, and logistical concerns (including cost factors) in the current health care arena. There are 85 numbered recommendations that have updated supporting evidence, of which 61 are revised and 12 are new. Noting that there can be multiple recommendation statements within a single numbered recommendation, there are 31 (13%) Grade A, 42 (17%) Grade B, 72 (29%) Grade C, and 101 (41%) Grade D recommendations. There are 858 citations, of which 81 (9.4%) are evidence level (EL) 1 (highest), 562 (65.5%) are EL 2, 72 (8.4%) are EL 3, and 143 (16.7%) are EL 4 (lowest). Conclusions: Bariatric procedures remain a safe and effective intervention for higher‐risk patients with obesity. Clinical decision‐making should be evidence based within the context of a chronic disease. A team approach to perioperative care is mandatory, with special attention to nutritional and metabolic issues.